Creating the Three Major International Music Teaching Methods Guidebook for Teaching Grade Three Students at Yichang Wulong Primary School, Hubei Province, China - Tian , Qu; Yodwised, Chutasiri (Journal of Roi Kaensarn Academi, 2024)
The purpose of the research are:1)To study the three major international music teaching methods form experts.2)To creat the Three Major International Music Teaching Methods guidebook.3)To use the three major international music teaching methods guidebook to teach students of Wulong Primary School in Yichang City.4)To evaluate the effect of teaching. This study employs a mixed-methods approach, combining both qualitative and quantitative research methods. A total of 24 students from Wulong Primary School in Yichang were selected as experimental subjects for the teaching experiment of the three major international music teaching methods. The researchers used qualitative methods to interview key informants and observe the learning conditions of the third-grade students at Wulong Primary School. During the development phase, quantitative analysis methods were used to describe the experimental design and perform statistical analysis of the results. The effectiveness of using the " Three Major International Music Teaching Methods Guidebook" was analyzed through three formative tests and a summative test. The research findings indicate:1)Through studying and interviewing key informants on the three major international music teaching methods, six suitable children's songs for third-grade students were selected. A teaching guide that integrates theory and practice was developed based on relevant literature on the three major international music teaching methods.2)The evaluation score for the "Guide to the Three Major International Music Teaching Methods" was 0.83, which is greater than 0.50. Key informants consider the design and implementation of the guide to be highly reliable, reasonable, and comprehensive. It meets the requirements of the "Teaching Guide Handbook" and can serve as a valuable reference for students learning the three major music teaching methods.3) Analysis of scores from three formative tests and the final summative test showed a significant improvement: all 24 students scored C or below in the first formative test, while in the summative test, all 24 students achieved scores of B or above. This demonstrates that the guide effectively enhances students' understanding of basic music knowledge and vocal performance.4)Overall, the creation of this guide has provided valuable teaching resources for primary music educators and students. It has made a positive contribution to the application of the three major international music teaching methods in Chinese primary music education.